Menstrual cycle disorders as an early symptom of energy deficiency among female physique athletes assessed using the Low Energy Availability in females questionnaire (LEAF-Q) - Witkos, J.; Luberda, E.; Blazejewski, G.; Strój, E. (PLOS ONE, 2024)
Physique competitions are weight-sensitive sports in which stage presentation, aesthetic appearance and posing ability of the athletes are judged rather than physical performance. The aim of this study was to assess low energy availability among female physique athletes by using the LEAF-Q. The study involved 104 females who were physique athletes. Monthly cycle disorders were reported in 58.65% of the women, that is periods stopped for three consecutive months or longer (amenorrhea). This situation occurred before the research was conducted in 43.27% of athletes and during the research in 15.38%. The physique athletes claimed that menstruation changes occurred when there was an increased exercise intensity, frequency or duration. Absence from training due to injury was reported by 27.88% of the women. The LEAF-Q identified 46.15% of the physique athletes as at risk (score = 8) of low energy availability and the physiological consequences related to RED-S. Women who had menstrual cycle disorders were younger and did more training per week. Among women with menstrual disorders, cramps or stomach ache which cannot be related to menstruation occurred more frequently (p = 0.004). Absence from training or lack of participation in competition due to injuries occurred more frequently in the score = 8 group (p = 0.024) thank the = score 8 group. In the score = 8 group menstruation changes, that is less bleeding or cessation of menstruation (p = 0.035), occurred more frequently when there was an increase in exercise intensity, frequency or duration (p = 0.002).